The role of in vitro chemosensitivity tests to predict the clinical efficacy of antineoplastic agents in genito-urinary tumors - (:unkn) unknown (My University, 1998)
OBJECTIVE: To develop an in vitro screening system to predict the response to treatment of common malignancies of the genito-urinary tract. MATERIAL AND METHODS: Flow cytometric analysis and cytotoxicity assays (trypan blue and lactic dehydrogenase colorimetric tests) were performed on hormone resistant prostate cancer cell line PC-3 and primary transitional cell carcinoma samples treated with different antineoplastic agents and their combinations. Apoptosis induced by different agents was also investigated by previously established criteria. RESULTS: There were 9 bladder tumors (47.4%) in the study group that displayed drug resistance to at least one antineoplastic agent. When the drugs were examined individually, there was resistance to cis-platinum in 3 patients (15.8%), methotrexate in 6 (31.6%), vinblastine in 7 (36.8%), epirubicin in 2 and adriamycin in 2 patients (10.5%). Stratification of patients according to the stage of the tumor revealed statistically significant difference between the superficial and invasive tumors in terms of drug resistance (p < 0.05). In prostate cancer cell line vinblastine treatment resulted in a significant increase in S phase fraction. Percent cytotoxicity by trypan blue exclusion test was 26.1% and was significantly higher than the control group (8.7%, p < 0.002). Also, an increase in apoptotic index after the treatment was observed (44.4% and 12.1%, respectively; p < 0.0001). CONCLUSION: Both toxicity assays showed a very good correlation (p < 0.005) and can be used to evaluate the effects of different antineoplastic agents on individual tumors.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Aged, 80 and over; Male; Predictive Value of Tests; Drug Screening Assays, Antitumor; Urogenital Neoplasms